Poverty, depression, and anxiety: Causal evidence and mechanisms - Ridley, Matthew; Rao, Gautam; Schilbach, Frank; Patel, Vikram (Science (American Association for the Advancement of Science), 2020)
Mental equilibrium is essential for an economically productive life in both industrialized and developing countries. Accumulating evidence shows that mental ill-health and poverty tend to be traveling partners, but which is the cause? Ridley et al. reviewed the literature on natural and controlled economic experiments involving individuals living in poverty. The authors sought to resolve the mechanisms whereby poverty triggers mental illness and how mental illness compounds poverty. Their results reveal the benefits of cash support and of low-cost therapeutic interventions for those suffering from mental illness under poverty. Science , this issue p. eaay0214 Why are people who live in poverty disproportionately affected by mental illness? We review the interdisciplinary evidence of the bidirectional causal relationship between poverty and common mental illnesses—depression and anxiety—and the underlying mechanisms. Research shows that mental illness reduces employment and therefore income, and that psychological interventions generate economic gains. Similarly, negative economic shocks cause mental illness, and antipoverty programs such as cash transfers improve mental health. A crucial step toward the design of effective policies is to better understand the mechanisms underlying these causal effects.